Application of the OpenCV-Python for Personal Identifier Statement - Sriratana, Witsarut; Mukma, Suppakorn; Tammarugwattana, Narin; Sirisantisamrid, Kaset (2018 International Conference on Engineering, Applied Sciences, and Technology (ICEAST), 2018)
Work attendance is one of the processes that either large or small companies need to be involved with. To reduce the time-consuming and improve the reliability of such process, this work proposes an alternative solution by applying the combinations of image processing and Viola Jones algorithm on the facial-employee database. The facial detection and recognition system shows the high accuracy over 90%. The proposed process not only improves the efficiency of the work attendance in term of data-collecting and data-analyzing but also possibly prevents the cheating of appearance compared to the old-fashion processes e.g. signing-paper or Radio Frequency Identification (RFID).